Advancements in bladder cancer immunotherapy: a focus on intravesical approaches - Tang, Xia; Yu, Tianlun; Tong, Hongxuan; Wu, Yufan (Frontiers in Pharmacology, 2025)
Recent advances in bladder cancer immunotherapy have shown promise, particularly in addressing limitations of the current gold standard, Bacillus Calmette-Guérin (BCG). Novel combinations, such as sasanlimab (a PD-1 monoclonal antibody) with BCG, have improved event-free survival in high-risk non-muscle-invasive bladder cancer (NMIBC). Intravesical anti-PD-1/PD-L1 agents like pembrolizumab and nadofaragene firadenovec have demonstrated efficacy and safety in BCG-unresponsive NMIBC, leading to regulatory approval. Additionally, BCG combined with immunostimulatory protein complexes (e.g., N-803) achieved high complete response rates while preserving quality of life. For muscle-invasive bladder cancer (MIBC) patients ineligible for cisplatin, neoadjuvant immunotherapy trials are exploring anti-PD-1/PD-L1 monotherapy or combinations with anti-CTLA-4 antibodies. The Pandore trial highlights the role of mucosal immunity in predicting response to systemic immune checkpoint inhibitors. Promising results have also been observed with intravesical oncolytic immunotherapy combined with systemic anti-PD-1 therapy in cisplatin-ineligible MIBC. These advancements underscore the potential of intravesical and systemic immunotherapies to improve bladder cancer outcomes and warrant further investigation.